FENOMENA MONDAY EFFECT PADA OVERNIGHT RETURN DAN INTRADAY RETURN SAHAM YANG TERGABUNG DALAM INDEKS LQ45 PERIODE 2018 - Martha Ayerza Esra; Pebiano Subagja (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2020)
As a trader must have a trading strategy that produces capital gains / losses from actual returns. Overnight returns and intraday returns are part of the actual return. But actually this return is by another factor. The influencing factor is the phenomenon of Monday's anomalous effect. The theory underlying this research is Random Walk, Efficient Market Hypothesis, Anomaly. Random Walk explains the random and unpredictable stock prices so that returns are generated randomly and cannot be predicted. The Efficient Market Hypothesis explains how securities or stock information is used to predict the price of a security or stock in the future so that the resulting return can be predicted. Anomaly explains the phenomena that deviate from the Efficient Market Hypothesis theory. This research was conducted on companies contained in the LQ 45 Index published on the Indonesia Stock Exchange in the period January 2018 - December 2018. By using the judgment sampling method, a sample of 34 companies was obtained with program SPSS 25. Data analysis techniques used were different paired sample tests. average. The results showed that the two different test of paired sample t-test used had fulfilled the normality test. Normality test results show all data are normally distributed. The significance value of the difference between the average return on Monday and the average return on non-Monday on return return is 0.119 with an average of -0.041 and the significance value is different between the average return on Monday with the average return on non-Monday the intraday return of 0.069 with an average of 0.1. The results show that (1) There is no difference between Monday return and non Monday return on intraday return.and (2) there is a difference between Monday return and non Monday return on intraday return.